2002
DOI: 10.2183/pjab.78.1
|View full text |Cite
|
Sign up to set email alerts
|

Remanent magnetization as a fossil of lightning current

Abstract: At the lightning, a strong magnetic field is induced around the path of the pulse current between the cloud and the ground. We investigated the remanent magnetization of the soil and ground material most likely acquired under this magnetic field. Both clockwise and counterclockwise rotating remanent magnetizations were found, which are believed to be corresponding to the positive and negative polarities of lightning current. The remanent magnetization can be a fossil of lightning current preserved in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These lightning-induced magnetic anomalies have posed problems for those attempting to survey regions for unexploded ordnance 22 or archaeological sites 23 , 24 . These previous studies have shown that CG strikes will impart a lightning-induced remanent magnetization (LIRM), which alters the natural remanent magnetization (NRM), and has been used in some studies to calculate characteristics (e.g., current, polarity) of the discharge 21 , 25 . Using current impulse experiments, one study 26 attributed changes in the magnetic properties of rocks to changes in mineralogy, where existing ferrimagnetic magnetite (Fe 3 O 4 ) transformed to antiferromagnetic hematite (α-Fe 2 O 3 ) through oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…These lightning-induced magnetic anomalies have posed problems for those attempting to survey regions for unexploded ordnance 22 or archaeological sites 23 , 24 . These previous studies have shown that CG strikes will impart a lightning-induced remanent magnetization (LIRM), which alters the natural remanent magnetization (NRM), and has been used in some studies to calculate characteristics (e.g., current, polarity) of the discharge 21 , 25 . Using current impulse experiments, one study 26 attributed changes in the magnetic properties of rocks to changes in mineralogy, where existing ferrimagnetic magnetite (Fe 3 O 4 ) transformed to antiferromagnetic hematite (α-Fe 2 O 3 ) through oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…While fulgurites (soils melted by lightning strikes) record magnetic fields associated with the lightning strike itself (> 1 T), through the process known as lightning-induced remanent magnetization (e.g. Sakai et al 1998;Sakai & Yonezawa 2002;Salminen et al 2013), it is not at all clear that the magnetic fields associated with solar nebula lightning currents can be maintained for the hours it took chondrules to cool. As such, chondrules melted by lightning probably would record the background magnetic field, but that is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…There have been reports of anomalous magnetization of rocks in volcanic terrains attributed to the effects of lightning (e.g., Matsuzaki and colleagues ); Sakai and colleagues examined lightning strokes on steel towers and in flat areas using the magnetic properties of ground surface materials . It was demonstrated that the lightning current polarity, current propagation into steel towers, and other characteristics can be investigated by using remanent magnetization.…”
Section: Introductionmentioning
confidence: 99%